RELASI KUASA, GROOMING, EKSPLOITASI GENDER REMAJA: ANALISIS SOSIOLOGI PENDIDIKAN ATAS MEMOAR BROKEN STRINGS - Detty Adithya Ayunda Putri Tandjung; Vieronica Varbi Sununianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Adolescence is a crucial transitional phase in identity formation vulnerable to imbalanced power relations and gender exploitation. This study aims to deconstruct the dynamics of exploitation in adolescents through the lens of the Sociology of Education by analyzing Aurélie Moeremans' memoir, Broken Strings (2025). Employing a descriptive qualitative method with a literature review approach, primary data were sourced from the memoir text through comprehensive document studies and analyzed using critical theory-based coding techniques. The analysis integrates Michel Foucault’s concepts of the Panopticon and Power/Knowledge to identify disciplinary mechanisms, alongside Radical Feminist theories from Adrienne Rich, Kate Millett, and Andrea Dworkin to examine bodily control and domestication. The findings reveal that perpetrators construct “regimes of truth” through religious doctrines and psychological manipulation (grooming) to paralyze the victim's autonomy. This study concludes that such phenomena represent the failure of educational and family institutions to foster Paulo Freire’s “conscientization” (critical consciousness), necessitating a transformation toward critical pedagogy as a preventive measure.